Cytokine responses to exercise and activity in patients with chronic fatigue syndrome: case–control study. (11th October 2017) - Clark, L. V.; Buckland, M.; Murphy, G.; Taylor, N.; Vleck, V.; Mein, C.; Wozniak, E.; Smuk, M.; White, P. D.
Summary: Chronic fatigue syndrome (CFS) is characterized by fatigue after exertion. A systematic review suggested that transforming growth factor (TGF)‐β concentrations are often elevated in cases of CFS when compared to healthy controls. This study attempted to replicate this finding and investigate whether post‐exertional symptoms were associated with altered cytokine protein concentrations and their RNA in CFS patients. Twenty‐four patients fulfilling Centers for Disease Control criteria for CFS, but with no comorbid psychiatric disorders, were recruited from two CFS clinics in London, UK. Twenty‐one healthy, sedentary controls were matched by gender, age and other variables. Circulating proteins and RNA were measured for TGF‐β, tumour necrosis factor (TNF), interleukin (IL)‐8, IL‐6 and IL‐1β. We measured six further cytokine protein concentrations (IL‐2, IL‐4, IL‐5, IL‐10, IL‐12p70, and interferon (IFN)‐γ). Measures were taken at rest, and before and after both commuting and aerobic exercise. CFS cases had higher TGF‐β protein levels compared to controls at rest (median (quartiles) = 43·9 (19·2, 61·8) versus 18·9 (16·1, 30·0) ng/ml) ( P = 0·003), and consistently so over a 9‐day period. However, this was a spurious finding due to variation between different assay batches. There were no differences between groups in changes to TGF‐β protein concentrations after either commuting or exercise. All other cytokine protein and RNA levels were similar between cases and controls. Post‐exertional symptoms and perceived effort were not associated with any increased cytokines. We were unable to replicate previously found elevations in circulating cytokine concentrations, suggesting that elevated circulating cytokines are not important in the pathophysiology of CFS. Abstract : In a case control study of circulating cytokines in chronic fatigue syndrome, we found a bimodal distribution of circulating transforming growth factor beta (TGF‐beta) (see figure). On examination for confounding, this was found to be a spurious finding, due to variation in laboratory technique.